Structure and Function of Parkin, PINK1, and DJ-1, the Three Musketeers of Neuroprotection - Trempe, Jean-Francois; Fon, Edward A. (Frontiers in Neurology, 2013)
Autosomal recessive forms of Parkinson’s disease are caused by mutations in three genes: Parkin, PINK1 and DJ-1. These genes encode for proteins with distinct enzymatic activities that may work together to confer neuroprotection. Parkin is an E3 ubiquitin ligase that has been shown to ubiquitinate substrates and to trigger proteasome-dependent degradation or autophagy, two crucial homeostatic processes in neurons. PINK1 is a mitochondrial protein kinase whose activity is required for parkin-dependent mitophagy, a process that has been linked to neurodegeneration. Finally, DJ-1 is a protein homologous to a broad class of bacterial enzymes that may function as a sensor and modulator of reactive-oxygen species, which have been implicated in neurodegenerative diseases. Here, we review the literature on the structure and biochemical functions of these three proteins.